Fish protein fertilizer serves as a sustainable alternative, improving soil properties, bamboo growth and shoots yield in Lei bamboo forests - Jiancheng Zhao; Huijing Ni; Bo Wang; Zhenya Yang (Scientific Reports)
Abstract Lei bamboo (Phyllostachys violascens ‘Prevernalis’) has high economic value, providing high yields of quality of bamboo shoots. Heavy use of chemical fertilizers and cover cultivation to produce off-season bamboo shoots results in soil degradation and a decline in soil productivity. This paper introduces an amino acid fertilizer, fish protein fertilizer, to replace a portion of chemical fertilizer, investigating the effects of different fertilizer combinations on bamboo growth, shoot yield, and soil properties, clarifying the growth-promoting mechanism of amino acid fertilizer. Results showed that after replacing 45 kg of compound fertilizer with 10 kg and 20 kg, respectively, of fish protein fertilizer (1) bamboo shoot yield increased by 23.24% and 26.19%, respectively; (2) leaf and root growth were enhanced, thick root proportion increased, and topsoil root proportion decreased; (3) soil pH, contents of available phosphate, soil organic carbon, microbial biomass carbon and microbial biomass nitrogen, soil enzyme activity increased; (4) the contents of nitrogen (N) and phosphate (P) in leaves increased, while the N/P and K/P decreased. Overall, amino acid fertilizer can promote microbial growth through supplying carbon sources and nitrogen sources, enhance soil enzyme activity, thus promote phosphorus activation and increase soil phosphorus effectiveness, and then expand the scale of root foraging and ultimately improve nutrients absorption and increase bamboo shoot yield.